A rare case report: an unusual fusion of mesiodens and incisors, supernumerary canine and missing mandibular lateral incisors - Mehta, Rina G.; Kamlesh B. Rami; Disha Bhatt; Kunal Thakkar; Niyati Thakkar (International Journal of Contemporary Pediatrics, 2023)
Supernumerary teeth are commonly encountered dental anomalies that affect the primary and early mixed dentition. They can lead to a range of pathological disturbances in the developing permanent dentition. Consequently, the patient has poor dental and facial aesthetics. The erupted or unerupted extra tooth located at the maxillary midline, between the central incisors is known as mesiodens. When diagnosed early, it can be treated properly with an excellent prognosis. The objective of this case report is to share knowledge about mesiodens and their management.